Analisis Biaya Kualitas Dalam Rangka Pengingkatan Produk Aulia Food Kabupaten Banggai - ari, arisanjaya doloan; Resti Riancana (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2026)
Quality Cost Analysis to Improve Product Quality at Aulia Food in Banggai Regency. This study aims to analyze quality costs at Aulia Food in Banggai Regency to improve the quality of its chips. Quality costs consist of four main components: prevention costs, appraisal costs, internal failure costs, and external failure costs. The research method used was a descriptive qualitative case study approach. Data were obtained through observation, interviews, and documentation of Aulia Food's production activities. The results indicate that Aulia Food has not systematically defined and categorized quality costs, resulting in suboptimal quality control. Prevention costs constitute the largest component of total quality costs, demonstrating the company's efforts to prevent defective products from occurring in the first place. Furthermore, quality costs have been shown to impact product quality improvement. With better quality cost management, Aulia Food can improve production efficiency, reduce failure costs, and enhance customer satisfaction. This study recommends regular quality cost recording to support more informed decision-making in product quality improvement.